REKONSTRUKSI NAMA PAPUA DAN IRIAN DALAM LINTASAN SEJARAH - Burdam, Yohanes; Winoto, Darmawan Edi; Rahman, Eka Yuliana (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2020)
This study attempts to reconstruct the use of the names Papua and Irian in the Indonesian Historical Path; and describe the dynamics of local struggle and the role of intellectuals before and after Indonesia's independence in interacting with the Republic of Indonesia (NKRI). The research uses a structuralism approach from Christopher Lloyd (1988), historical methods from Marc Bloch (1988), and the "Collective Active" theory from Charles Tilly (1978, 1993) for the explanation of facts. Data is collected by studying documents (archives, books, and interviews). Data collected from archives and interviews were carried out by historical criticism, and interpreted into facts which were then assembled into historical accounts of the process of naming Papua and Irian and its relation to the local dynamics of intellectual struggles before and after Indonesia's independence to integrate with the Republic of Indonesia. The results of the study revealed that the name "Papua" was given Ortez de Retes and then was used by the Dutch for the large island together with the population and their culture. However, the name Papua by the Netherlands tends to be negative meaning for local residents. Over time, the intellectuals emerged thinking and struggling to find a name to replace the name Papua with Irian.